Strategic Human Resources Development as a Catalyst for Performance Optimization - Ade Maharani; Yulia Hanoselina (Al-Qalam Institue, 2025)
This study explores strategies to enhance human resource (HR) performance at the Water Resources and Construction Development Agency (SDABK) of West Sumatra Province, in response to declining employee numbers, unmet performance targets, and low public satisfaction. Guided by Noe et al.’s (2024) framework—covering goal-setting, feedback, work environment, recognition, and continuous development—the research adopts a qualitative, descriptive approach using interviews, documentation, and triangulation for data validation. Findings reveal that while the agency has successfully fostered a supportive work environment and implemented recognition systems, key areas such as clear goal-setting, constructive feedback, and ongoing training remain underdeveloped. Challenges include organizational resistance to change, limited budgets, reduced technical staff, and external factors like natural disasters. These obstacles reflect deeper structural, technical, and cultural issues. The study underscores the importance of strategic HR management in improving public sector performance. By addressing existing gaps, the SDABK has the potential to enhance service quality and contribute more effectively to regional infrastructure development.